Geodiversity and Geo-education in the constrution of tourist and leisure territories: the case of Estrela Aspiring Geopark (EAG). - Fernandes, Magda (2018)
Geodiversity has an intrinsic enormous scientific value in allowing us to understand the evolution of our Planet. In this sense, it is necessary to implement strategies to preserve geodiversity, through geoconservation. In order to disseminate and promote geological heritage, some territories seek to develop educational programs that promote direct contact with geoheritage, contributing to the recognition of its importance and consequently of the need for its conservation. In implementing educational promotion strategies, with the use of properly prepared guides and appropriate educational materials, teachers are encouraged to promote field lessons at different levels of education, contributing to increasing the interest in geosciences, as well as for a better understanding of other phenomena occurying on Earth. With the objective of promoting the development of value-added activities, based on geodiversity, we have seen a tourist appropriation of these resources, giving rise to geotourism strategies. We are thus faced with a potential form of sustainable tourism that can contribute to the economic development of many regions, while respecting sustainability criteria. The conservation of geological heritage takes place through the implementation of key methods, such as inventories, with evaluation of its scientific, educational, cultural and tourist value; the implementation of signage, publications (articles, leaflets, guides and maps), audiovisual media (promotional videos), exhibitions, and interpretative panels accessible to all (in several languages, including Braille) and the establishment of interpretative routes. In this context, this presentation aims to identify different strategies of valorization, promotion and appropriation of courses, placing them at the service of the community and tourist development. Examples of the Aspiring Geopark Estrela, a privileged space for geotourism and geo-education will be used. The territory of Aspiring Geopark Estrela, comprising 9 municipalities, (Guarda, Seia, Gouveia, Celorico da Beira, Fornos de Algodres, Manteigas, Belmonte, Covilhã and Oliveira do Hospital), has its agglutinating element in Serra da Estrela, with geological heritage of national and international scientific relevance. The Estrela is part of the Iberian Central Cordillera and the first barrier to the moist air masses from the Atlantic that enter southwest Europe. The mountain with a summit plateau between 1,400 and 2,000 m ASL was extremely sensitive to the cold periods of the Pleistocene, having developed extensive glacial and periglacial features. These, interplay with the Cenozoic geomorphological heritage marked by large and medium scale morphotectonic elements afecting the dominant granite terrains, as well as the metasediments, as well as with the remnants of planation surfaces and deep weathering. The landscape is a complex and rich geological and geomorphological mosaic with major controls on climate, hydrology, ecosystems, culture and economy that extend far beyond the Aspiring Estrela Geopark region. We will show examples of the different educational programs that are being currently promoted and directed to the disciplinary areas of the Natural Sciences, Biology/Geology and Geography, of the basic and secondary education. Our approach allows for an interdisciplinarity with other areas of knowledge, such as, for example, History and Archeology.